2022
DOI: 10.21608/ejhm.2022.273048
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Some RBCs and Platelets Indices with Outcome of Critically Ill Children Admitted to Pediatric Intensive Care Units

Abstract: Background: Platelet and Red blood cell indices ratios serve as a simple and convenient stratification tool for illness severity predictors in pediatric intensive care unit (PICU) mortality. The aim of the current study was toevaluate the ability of red cell distribution width (RDW) and platelet indices and ratios to predict mortality. Patients and methods: A prospective, observational study was conducted on 99 critically ill children of both sexes admitted to PICU of Benha University Hospitals and Benha Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Conversely, there was a significant decrease in platelet count and Plateletcrit (PCT) in nonsurvivors, also with a p-value of less than 0.001. These findings align with the results obtained by Aliaa Mohammed Diab et al [9] in their investigation correlating certain red blood cell (RBC) and platelet indices with the outcomes of critically ill children in pediatric intensive care units. Their study identified significant associations, particularly with Platelet count (PLT) (*10^3 /ml) (p value = 0.002), Plateletcrit (PCT) (%) (p-value = 0.005), and Mean Platelet Volume (MPV) (FL) (p-value = 0.158).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Conversely, there was a significant decrease in platelet count and Plateletcrit (PCT) in nonsurvivors, also with a p-value of less than 0.001. These findings align with the results obtained by Aliaa Mohammed Diab et al [9] in their investigation correlating certain red blood cell (RBC) and platelet indices with the outcomes of critically ill children in pediatric intensive care units. Their study identified significant associations, particularly with Platelet count (PLT) (*10^3 /ml) (p value = 0.002), Plateletcrit (PCT) (%) (p-value = 0.005), and Mean Platelet Volume (MPV) (FL) (p-value = 0.158).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study as regarding to sex there was no significant difference between the two main studied groups ~ 31 ~ with (p-value=0.168) with male predominance in both groups. This aligns with the findings of Aliaa Mohammed Diab et al [9] , who conducted a prospective observational study on 99 critically ill children admitted to pediatric intensive care units (PICUs) at Benha University Hospital and Benha Children Hospital. The study, conducted between April 1, 2018, and September 30, 2018, revealed no statistically significant difference in sex (p-value 0.89).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations